ANALISIS KADAR DEBU TERHIRUP DAN GANGGUAN PERNAFASAN PADA TENAGA KERJA DI BAGIAN PRODUKSI SUATU INDUSTRI KAYU - Ineke Puspitasari; Hadi Suryono; Nur Haidah (GEMA LINGKUNGAN KESEHATAN, 2016)
UD. Kartika Jasa is a home wood processing industry. In addition to providing product, it also creates negative impact of generating dust that in production process, the labors are at risk of exposure to dust. In an amount that exceeds TLV, dust can cause health problem for workers, one of which is respiratory disorder complaint. The purpose of this study was to determine relationship between level of inhaled dust with respiratory disorders complaint. This research is Cross Sectional analytical research with 20 workers as samples. Method af data collection was carried out by observation of inhaled dust. Data analysis used Fisher’s exact test. From the result of inhaled dust level measurement, it is found out that most of the labor force were not eligible (55.0%) with severe respiratory disorders complaint (70.0%). Most of the labor force aged 30 years (60.0%), length of labor 10 years (55.0%), had smoking habit (75.0%) did not have habit of wearing PPE at all (65.0%). In inhaled dust level variable, age, years of smoking habit and the habit of wearing PPE affected respiratory disorder complaint experienced by workforce with ρ 0,05. The research concludes that there was a relationship between the level of inhaled dust and respiratory disorder complaint on labor. Effort to control technically, administratively, and the use of PPE in the workplace is required.Keywords : Dust Concetration, respiratory disorders